Gender Disparities among Scheduled Tribes in Manipur: Trends and Determinants - Ningomban Sanajaoba Singh (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This study examines gender disparities among Scheduled Tribes (STs) in Manipur, India, focusing on sex ratio, literacy rates, and work participation rates (WPR) using Census data from 1991, 2001, and 2011. The findings indicate a rising ST sex ratio, consistently exceeding the national average, attributed to egalitarian social structures and limited access to sex-selective technologies. While literacy rates have improved for both genders, a persistent yet relatively smaller gender gap remains, influenced by traditional norms and infrastructural limitations. The WPR gender gap among STs is narrower than in other social groups, as women actively engage in agriculture and economic activities out of necessity and cultural acceptance. Some tribal communities exhibit a reversed gender gap, with higher female literacy and WPR, while others continue to face disparities. The study highlights the need for targeted policies, enhanced infrastructure, and community-driven initiatives to foster gender inclusivity among Scheduled Tribes in Manipur.